Microsoft Office XP - Gary B. Shelly (Cengage Learning, Inc, 2002)
Part of the highly successful Shelly Cashman Series, Microsoft Office XP Introductory Concepts and Techniques provides step-by-step instructions accompanied by full-color screen shots, helping students learn basic Office XP skills quickly and easily